The Expression, Regulation, and Biomarker Potential of Glypican-1 in Cancer - Wang, Sen; Qiu, Yudong; Bai, Bing (Frontiers in Oncology, 2019)
Glypican-1 (GPC-1) and other glypicans are a family of heparan sulfate proteoglycans. These proteins are highly expressed on cell membrane and in the extracellular matrix, mainly functioning as modulators of growth factor signaling. Some of them are abnormally expressed in cancer, possibly involved in tumorigenesis, and detectable in blood as potential clinical biomarkers. GPC-1 is another glypican member that has been found to be associated with certain cancers, and has increasingly interested the cancer field. Here we provide a brief review about GPC-1 in its expression, signaling and potential as a cancer biomarker.